Advances in the structure and composition design of zinc anodes for high performance zinc ion batteries. Issue 15 (13th July 2022) - Li, Quanyu; Chen, Yuejiao; Wang, Han; Yu, Huaming; Wei, Weifeng; Ji, Xiaobo; Qu, Baihua; Chen, Libao
Abstract : In this review, we classify in detail the recent achievements in structural and composition design, including intrinsic zinc metal anodes, metal-based anodes, alloy-based anodes, carbon-based anodes, MXene-based anodes and some novel composite anodes. Abstract : Aqueous zinc-ion batteries (ZIBs) are considered to be a kind of promising candidate for next generation grid-scale energy storage due to their high capacity, environmental benignity, high safety and low cost. However, practical application of ZIBs has been plagued by uncontrollable dendrite growth, corrosion and hydrogen evolution which lead to the miserable durability and low coulombic efficiency of Zn anodes. The design of the functional structure and composition provides an effective pathway to tackle these challenges and develop high-performance Zn anodes. In this review, we classify in detail the recent achievements in structural and composition design, including intrinsic zinc metal anodes, metal-based anodes, alloy-based anodes, carbon-based anodes, MXene-based anodes and some novel composite anodes. A scientific understanding of design principles to guide the strategies to suppress these problems is emphasized first. Deposition behaviors of zinc in these constructions and their corresponding action mechanisms are systematically summarized. Besides, with great mechanical strength and flexibility, advanced electrode materials have broadened prospects in wearable devices, which is also one of our concerns. Finally, the challenges and opportunities of zinc anode structure design are prospected. This review will provide potential directions and perspectives for the rational structure design of high-performance ZIBs.